Maternal exercise during pregnancy modulates mitochondrial function and redox status in a sex-dependent way in adult offspring's skeletal muscle. (5th April 2022) - Hözer, R.M.; dos Santos, B.G.; August, P.M.; Rodrigues, K.S.; Maurmann, R.M.; Flores, E.B.; Matté, C.
Abstract: Maternal exercise has shown beneficial effects on mother and child. Literature confirm progeny's cognition improvement, and upregulation in neurotrophins, antioxidant network, and DNA repair system. Considering that there is a lack of information demonstrating the impact of maternal exercise on offspring's skeletal muscle, we aimed to investigate the mitochondrial and redox effects elicited by maternal swimming. Adult female Wistar rats were divided into three groups: control sedentary, free swimming, and swimming with overload (2% of the body weight). Exercised groups were submitted weekly to five swimming sessions (30 min/day), starting 1 week prior to the mating and lasting to the delivery. Gastrocnemius and soleus muscle from 60-day-old offspring were analyzed. Our results clearly showed a sex-dependent effect. Male soleus showed increased mitochondrial functionality in the overload group. Female muscle from the overload group adapted deeply. Considering the redox status, the female offspring delivered to overload exercised dams presented reduced oxidants levels and protein damage, allied to downregulated antioxidant defenses. We also observed an increase in the mitochondrial function in the gastrocnemius muscle of the female offspring born from overload exercised dams. Soleus from female delivered to the overload exercise group presented reduced mitochondrial activity, as well as reduced reactive species, protein carbonyls, and antioxidant network, when compared to the male. In conclusion, maternal exercise altered the redox status and mitochondrial function in the offspring's skeletal muscle in a sex-dependent way. The clinical implication was not investigated; however, the sexual dimorphism in response to maternal exercise might impact exercise resilience in adulthood.